"It is like a jungle gym, and everything is under construction": The parent's perspective of caring for a child with a rare disease. (8th November 2018) - Currie, Genevieve; Szabo, Joanna
Abstract: Descriptive title: Parents of children with rare diseases face pervasive challenges in meeting medical and social care needs. Existing research on the parents' experience of caring for a child with a rare disease is limited. This paper offers suggestions for better supporting families living with rare disease as well as possible avenues of future research. Background: Parents of children with rare diseases face pervasive challenges in meeting medical and social care needs. Existing research on the parent's experience of caring for a child with a rare disease is limited. Methods: An interpretive phenomenological approach was applied in this inquiry. Fifteen parents of children with rare diseases participated in semistructured interviews. Results: Interpretive thematic analysis revealed that due to the rarity of the disease and an overall lack of knowledge of the disease, there is an increase in the burden on the family in relation to "rarity" in addition to "disability." Four insights were also revealed: (a) Parents often know more about the disease then Health Care providers, and this leads to entanglements in communication and collaboration as experts and parents; (b) there is lack of coordination of care between providers and services caring for children with rare diseases; (c) there is a gap in accessibility to government supports; and (d) due to fragmented care, parents must fill the aforementioned gaps by juggling multiple roles including that of advocate, case manager, and medical navigator. Conclusion: This paper offers suggestions for better supporting families living with rare disease as well as possible avenues of future research.